EXPLORING FISCAL DECENTRALIZATION IN INDONESIA: THE IMPACT OF SPECIAL AUTONOMY FUNDS ON THE ECONOMIES OF ACEH, PAPUA, AND WEST PAPUA - Rahman, Syahrir (ipdn, 2024)
Fiscal decentralization represents a pivotal strategy by the Indonesian Government to promote equitable development and alleviate regional disparities. Within this framework, Special Autonomy Funds, integral to the Transfer to Region scheme, act as a critical policy instrument. Despite numerous studies, the definitive role of fiscal decentralization on regional economic dynamics still needs to be solved. This research endeavors to deepen the understanding of fiscal decentralization's impact in Indonesia by examining the effects of the Special Autonomy Funds on the regional economy. Specifically, it assesses how these funds influence the Gross Regional Domestic Product (GRDP) Per Capita at Current Prices (ADHB) across Aceh, Papua, and West Papua provinces. The results show a significant impact of the Special Autonomy Funds on the GRDP Per Capita ADHB, with a high R2 of 94.2% by using panel regression analysis. Keywords: Fiscal Decentralization, Transfer to Region, Special Autonomy Funds, Regression Analysis.